Dampak Fintech Illegal dan Penegakan Hukumnya di Indonesia - Martinus Ahmad; Ahmad Abdul Ghoni; Sri Wahyuni (Jurnal Hukum Sasana, 2023)
Fintech, short for financial technology, has brought significant changes to the way we conduct financial transactions, access financial services, and manage personal finances. However, the rapid growth of Fintech has also created opportunities for illegal practices in this sector. In this abstract, we will discuss the impact of illegal Fintech on the economic level of society. Illegal fintech refers to illegal practices carried out by companies or individuals operating in the Fintech sector without proper permits or regulation. The negative impact of illegal Fintech can be seen from several perspectives. Illegal practices within the Fintech sector can have a negative impact on the economy as a whole. This can reduce public confidence in the Fintech industry in general and hinder the growth of sectors that actually have great potential to support economic development. Illegal fintech often targets people who do not have adequate access to formal financial services. As a result, already vulnerable communities may become targets of these illegal practices and face higher risks of exploitation and fraud. To overcome the impact of illegal Fintech on the economic level of society, several actions can be taken including; The government needs to improve the regulatory framework and supervision of the Fintech sector to reduce illegal practices. Fintech companies must be granted proper licenses and closely monitored to ensure compliance with applicable regulations. Public education and awareness about the risks of illegal Fintech is very important. The public needs to be provided with sufficient information on how to identify illegal Fintech and report it to the competent authorities.